Enhancing maritime management efficiency: Developing a next-generation Android App to review agent satisfaction level in sailing approval procedures - Hasnur, Juliandri; Nazarwin, Nazarwin; Kurniawan, Edi; Nugraha, Markus Asta Patma (Universitas Negeri Padang, 2024)
This research was conducted to develop a state-of-the-art Android application to measure the satisfaction of agents involved in the sailing approval process. The main objective is to improve the efficiency and satisfaction of ship agents during the process of issuing sailing permits at the Harbour Master and Port Authority, Teluk Bayur, Sumatera Barat, Indonesia. This research involves the design and development of an Android-based survey application, which has undergone expert validation and usability testing to ensure its effectiveness. This research used the Plomp development model and involved 21 people who made arrangements at the Port Authority office as research subjects. The results of the study show that the newly developed application is valid for assessing agent satisfaction in managing the services for issuing Sailing Permits, with a material validity of 0.87 and a media validity of 0.88. Furthermore, the results of the agents' evaluation show that the Android-based agent satisfaction survey is very practical, with a practicality rate of 93%. This study also outlines the limitations encountered during the research and proposes future recommendations to improve the research. In conclusion, this research highlights the practicality and validity of the developed Android-based Agent Satisfaction Survey application.